Synthesis of aryl and heteroaryl tetrafluoro-λ6-sulfanyl chlorides from diaryl disulfides using trichloroisocyanuric acid and potassium fluoride. Issue 8 (6th March 2019) - Saidalimu, Ibrayim; Liang, Yumeng; Niina, Kiyoteru; Tanagawa, Kazuhiro; Saito, Norimichi; Shibata, Norio
Abstract : A catalyst-free method for the synthesis of (Het)ArSF4 Cl by using trichloroisocyanuric acid and potassium fluoride in acetonitrile is disclosed. Abstract : We present a catalyst-free method for the synthesis of aryl and heteroaryl tetrafluoro-λ 6 -sulfanyl chlorides (Ar-SF4 Cl) by using trichloroisocyanuric acid and potassium fluoride in acetonitrile. The method has wide substrate generality and proceeded well with high yields even in the absence of acid catalysts. The preparation of meta - and para -SF4 Cl-substituted pyridines using TCCA was achieved for the first time.